Phosphate Nutrition of Rhizobium spp - Beck, Douglas P. (1984)
This study was conducted to determine the behavior of 40 strains from six species of Rhizobium in liquid defined media containing orthophosphate at levels likely to be encountered naturally, ranging from the high concentrations expected in nodules and artificial media to the low concentrations of soil solutions. Storage capacity in strains with high levels (2 mM) of P and ability to utilize this stored P for growth after transfer to low levels (0.06 μM) of P varied with each strain. Storage varied from about 1 to 2% P (dry weight) for all strains, with the number of generations supported dependent on the quantity of P stored and on the utilization efficiency. The ability to store P at high levels is probably less important than the uptake and utilization efficiency of P supplied at low levels. Strains varied greatly in tolerance to low levels of P maintained in solution by an iron oxide buffering system. Differences in growth rate at low levels of P were large enough to be agronomically important.